A prospective RCT comparing combined chromoendoscopy with water exchange (CWE) vs water exchange (WE) vs air insufflation (AI) in adenoma detection in screening colonoscopy. Issue 4 (May 2019) - Leung, JW; Yen, AW; Jia, H; Opada, C; Melnik, A; Atkins, J; Feller, C; Wilson, MD; Leung, FW
Background: A low adenoma detection rate (ADR) increases risks of interval cancers (ICs). Proximal colon flat polyps, e.g. serrated lesions (SLs), are difficult to find. Missed proximal colon flat lesions likely contribute to IC. Aims: We compared chromoendoscopy with water exchange (CWE), water exchange (WE) and air insufflation (AI) in detecting adenomas in screening colonoscopy. Methods: After split-dose preparation, 480 veterans were randomized to AI, WE and CWE. Results: Primary outcome of proximal ADR (55.6% vs 53.4% vs 52.2%, respectively) were similar in all groups. Adenoma per colonoscopy (APC) and adenoma per positive colonoscopy (APPC) were comparable. Detection rate of proximal colon SLs was significantly higher for CWE and WE than AI (26.3%, 23.6% and 11.3%, respectively, p = 0.002). Limitations: single operator; SLs only surrogate markers of but not IC. Conclusions: When an endoscopist achieves high-quality AI examinations with overall ADR twice (61.6%) the recommended standard (30%), use of WE and CWE does not produce further improvement in proximal or overall ADR. Comparable APC and APPC confirm equivalent withdrawal inspection techniques. WE alone is sufficient to significantly improve detection of proximal SLs. The impact of increased detection of proximal SLs by WE on prevention of IC deserves to be studied. This study is registered at ClinicalTrial.gov (NCT#01607255).